Harnessing universal chemical markers to trace the provenance of marine animals. (November 2022) - Doubleday, Zoë A.; Martino, Jasmin C.; Trueman, Clive
Graphical abstract: Highlights: Introducing the concept of universal chemical markers. Global trends in oxygen isotopes within marine biominerals illustrate concept. A new approach to tracking a greater range of marine species and seafood products. Abstract: Identifying the provenance of marine animals yields fundamental data on a species' ecology and life history and enables the geolocation of individuals for food forensic applications. However, many provenance methods are resource-intensive and developed on a species-specific basis. Here we discuss how natural chemical markers with predictable spatial patterns and common expression among species could be used as provenancing tools that are universally applicable to many species. To demonstrate the universal marker concept, we focus on stable oxygen isotopes bound within calcium carbonate biominerals. In doing so, we compiled a global database of oxygen isotope values to illustrate universal latitudinal patterns across key marine taxa. We then discuss how this concept could be integrated within a spatial modelling framework and applied to tackle the environmental challenge of seafood provenance. By developing universal markers we have the opportunity to trace a greater range of species to support their conservation and management.